Digital transformation for business sustainability and growth in emerging markets - Dadwal, Sumesh; Kumar, Pawan; Verma, Rajesh; Kumar, Sunil (Emerald Publishing Limited, 2025)
Digital transformation in organisations can improve business agility, operational efficiency, customer service, and contribute to sustainability initiatives. Digital transformation isn't always easy to implement; organisations can experience resistance to change and a lack of skilled employees. While there is extensive research on digital transformation, there is a lack of research that focuses specifically on emerging markets. Digital Transformation for Business Sustainability and Growth in Emerging Markets explores the rich context of emerging markets, which present unique challenges for digital transformation, including cultural differences, limited access to technology, and regulatory hurdles in emerging markets. The book includes topics like Turbo boosting, industry 4.0, quantum, computing, Generative AI Adoption Sustainable Digitalisation etc and their role in sustainability of the business. Digital Transformation for Business Sustainability and Growth in Emerging Markets addresses the challenges and opportunities afforded by digital transformations to help businesses build a clear strategy, invest in building digital capabilities, and foster a culture of innovation and continuous improvement.